2010
DOI: 10.1375/ajgc.20.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Cyberbullying in School Using the Quality Circle Approach

Abstract: C yberbullying has become a significant area of concern, yet research is still at an early stage. The Quality Circle approach allows explorative analysis of cyberbullying in school settings by identifying issues for further consideration. In this study of cyberbullying in one UK secondary school, Quality Circle participants were required to establish a small anti-bullying taskforce, and then with the guidance of a facilitator, embark on a problem-solving exercise over a period of time. The process involves ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 7 publications
0
32
0
9
Order By: Relevance
“…There are a number of possibilities for why these differences exist. One possibility is that a larger number of nationwide interventions have been conducted in European countries than in North America (e.g., Genta, Brighi, & Guarini, 2009;Livingstone & Haddon, 2009;Paul, Smith, & Blumberg, 2010), and, thus, the overall prevalence in these countries might be lower than in North America. Indeed, we tested this possibility with available data from Table 1, and the difference in average CV prevalence rates between European/Australian samples (M ϭ 16.34) and North American samples (M ϭ 21.6) is marginally significant, t(54) ϭ 1.56, p ϭ .06 (one-tailed).…”
Section: Moderators Of the Cb/cv Relationsmentioning
confidence: 99%
“…There are a number of possibilities for why these differences exist. One possibility is that a larger number of nationwide interventions have been conducted in European countries than in North America (e.g., Genta, Brighi, & Guarini, 2009;Livingstone & Haddon, 2009;Paul, Smith, & Blumberg, 2010), and, thus, the overall prevalence in these countries might be lower than in North America. Indeed, we tested this possibility with available data from Table 1, and the difference in average CV prevalence rates between European/Australian samples (M ϭ 16.34) and North American samples (M ϭ 21.6) is marginally significant, t(54) ϭ 1.56, p ϭ .06 (one-tailed).…”
Section: Moderators Of the Cb/cv Relationsmentioning
confidence: 99%
“…Paul, Smith, and Blumberg (2010) discussed the Quality Circle approach as a way to combat cyberbullying in schools. This approach is student-centered and focuses on the students coming together in groups and taking a three part approach around cyberbullying: analyzing the problems around cyberbullying, developing solutions around cyberbullying, and then developing solutions that would work to combat the issue of cyberbullying in the school.…”
Section: Cyberbullying Prevention and Intervention Internationallymentioning
confidence: 99%
“…Together, adequate intervention and prevention strategies can be developed and implemented. Furthermore, use of strategies from other countries, like quality circles (Paul et al, 2010), should be explored in the United States. The strategies mentioned in this study-such as using freshmen retreats and orientations with refreshers should be further explored.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…In a previous case study in an English secondary school (Paul, Smith, & Blumberg, 2010), QCs were implemented by six groups over a one-term period, from March to July 2009. Analysis of the information reported by the QCs showed that general bullying most often occurred as verbal bullying in the form of 'cussing', namely insults.…”
Section: Previous Research Using Qcsmentioning
confidence: 99%